Fungi for the bioremediation of pharmaceutical-derived pollutants: A bioengineering approach to water treatment - Akerman Sánchez, Galit (2021)
The excessive amount of pharmaceutical compounds (PhCs) released into aquatic environments poses a risk to humans, wildlife, and environmental health. It is a serious problem that requires urgent attention. In this work, we review various PhCs detected in water treatment plants. We propose that fungi, particularly white-rot fungi (WRF), can be used for their bioremediation and describe the main mechanisms used for degrading this type of emerging pollutants; however, we also highlight the need to prospect for new fungal models. A conceptual proposal is made to develop an immobilization device containing a consortium of fungal species that can be placed in wastewater treatment plants (WWTP). We consider that this device would allow more efficient bioremediation of PhCs and address an environmental problem that remains neglected.